Evidence for two types of lateral interactions in visual perception of temporal signals - Teixeira, Claudio E. C.; Salomao, Railson C.; Rodrigues, Anderson R.; Horn, Folkert; Silveira, Luiz Carlos L.; Kremers, Jan (Journal of Vision, 2014)
The aim of this work was to investigate the mechanisms of lateral interactions involved in flicker perception. Furthermore, the spatial properties of the monoptic and dichoptic components of these mechanisms were studied. We quantified the perceived flicker strength (PFS) in the center of a test stimulus, which was simultaneously modulated with a surround stimulus of variable size. The modulation depth of a separate stimulus, identical to the center test stimulus but without the surround, was determined using a two-alternative forced choice procedure. Using LCD goggles synchronized to the frame rate of a CRT screen, the center and surround of the test stimulus were presented either monoptically or dichoptically. In the monoptic condition, center-surround interactions have subcortical and cortical origins. In the dichoptic condition, center-surround interactions must have a cortical origin. The difference between the dichoptic and the monoptic data is an estimate of the contribution of the subcortical mechanisms. At each condition (surround stimulus size; monoptic or dichoptic presentation), the PFS was measured for phase differences between center and surround stimuli. The PFS changed systematically with phase difference. It also was observed that the PFS in the center stimulus changed merely be the presence of a surround stimulus independently of the center-surround phase difference. We propose that this is a phase-independent mechanism related to contrast adaptation owing to the presence of surround modulation. Our data suggest that both phase-dependent and -independent mechanisms have cortical and subcortical origins. There were no systematic differences between the spatial properties of subcortical and cortical components involved in PFS modulation.
EVALuna2:21165